Liminal Spaces, and Identity Transformations in South Asian Literatures and Arts. Essays in Honour of Professor Alexander Dubyanskiy - Rossi, Paola M. (Consonanze, 2023)
The present volume is a collection of 16 papers presented at the International Seminar 'Liminal Spaces, and Identity Transformations in Indian Cultural History' in Milan, in September 2019, when we were on the brink of a historical change unknowingly. And afterwards, during the pandemic experience, exploring liminality, as category of reality applied to Indian culture and especially to art and literature, appeared to be a means to cope with an emergency the likes of which had never been seen before. Obviously, this work does not aspire to be exhaustive, nonetheless, the heterogeneity of the contributions offers a multifaceted perspective: in actual fact, since liminality implies potentially myriads of interpretations, it appears to provide us with one of the main keys to addressing the entanglement of reality, especially the complexity of the Indian civilization, past and present. The focus is particularly on the literary and artistic aspects of such an extraordinary cultural heritage, from the Vedic period up to modernity; literature and arts are the lens through which variegated anthropological issues, crossing different historical phases, are investigated: firstly, the ritual question, in compliance with van Gennep and Turner's approach, but also religious experiences, sovereignty and violence, dialectics of identity, social dynamics, gender identity, etc. Literature and arts, but still by means of their own aesthetic devices, mirror critical points characterising such issues, as if poetry and artwork, zooming in on specific transition elements, were themselves on the threshold of manifold layers of reality, able to pass through their interstitial discontinuities. Finally, it is a great honour to dedicate such a volume to the memory of Professor Alexander Dubyanskiy (1941-2020), eminent scholar in Indian literature, especially in Tamil poetry, who experienced multiple aspects of liminality both of the South Asian culture and life.